Exploring the intersection of big data and open innovation: Synergies and challenges in emerging contexts - Cândido, A. C.; Seclen-Luna, J. P.; Sousa, C. (Journal of Innovation Management, 2025)
This study explores the symbiotic relationship between Big Data and Open Innovation. They work together to accelerate innovation and generate value for organizations. Different sectors and organizations go through decision-making processes that range from operational and routine aspects to managerial and strategic decisions, such as the implementation of a new product or the purchase of a new production unit. All these decisions require data and information that can mitigate risks and support choices. This study draws insights from real-world case studies, emphasizing the transformative potential of Big Data for open innovation. It analyzes evidence of the use of Big Data in Open Innovation practices in a group of Peruvian software companies. The results show the gap in the use of Big Data to support collaborative practices in the sample. In fact, often, those companies do not see a direct relationship between Big Data experience and the adoption of Open Innovation practices. The findings underscore the need for integrated approaches and suggest that bridging the gap between Big Data and Open Innovation offers a promising avenue for thriving in an information-rich environment.